Effect of sustained released metformin therapy on phenotypic and biochemical markers of insulin resistance in polycystic ovary syndrome in South Indian women - Kumar, Rama Nagendra; Seshadri, Krishna G.; Pandurangi, Monna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in young women. Insulin resistance (IR) may play a substantial part in the pathogenesis of PCOS, which leads to type 2 diabetes mellitus (T2DM), cardiovascular disorders and ovarian cancer. Metformin is an insulin sensitizing agent, however its role in PCOS is still controversial. Methods: Sixty women newly diagnosed with PCOS and healthy age matched controls between 18 to 45 years were enrolled after obtaining informed consent. Women in the PCOS group were started on metformin-SR 1gram orally, which was then increased to 1.5 grams after two weeks and continued for 6 months. Fasting blood sugar (FBS), fasting insulin (FI), SHBG, TT, free androgen index (FAI), homeostatic model assessment of Insulin resistance (HOMA-IR), homeostatic model assessment of β- cell function (HOMA-B), homeostatic model assessment of Insulin sensitivity (HOMA-S) and quantitative insulin sensitivity check index (QUICKI) were measured in the control group as well as PCOS group before and after metformin therapy. Results: After six months of metformin-SR therapy, PCOS group showed significant reduction in FI, HOMA-IR, HOMA- β, HOMA-S QUICKI, TT and FAI and significant increase in SHBG levels. Conclusions: Six months of metformin-SR therapy favorably altered markers of IR, TT, SHBG, anovulation and hyperandrogenism in normoglycemic women with PCOS.